2024
DOI: 10.1515/revneuro-2023-0155
|View full text |Cite
|
Sign up to set email alerts
|

The role of long noncoding RNAs in amyotrophic lateral sclerosis

Darya Rajabi,
Shaghayegh Khanmohammadi,
Nima Rezaei

Abstract: Amyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative disease with a poor prognosis leading to death. The diagnosis and treatment of ALS are inherently challenging due to its complex pathomechanism. Long noncoding RNAs (lncRNAs) are transcripts longer than 200 nucleotides involved in different cellular processes, incisively gene expression. In recent years, more studies have been conducted on lncRNA classes and interference in different disease pathologies, showing their promising contribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 126 publications
0
2
0
Order By: Relevance
“…Several tools for studying lncRNAs have been developed so far 33 , but a comprehensive understanding of their role and involvement in human diseases is still lacking. Despite a very few reports mentioned a role or a function directly attributed to lncRNAs in this disease 21,22,34,35 , some authors recently reported a differential expression of lncRNAs in ALS transcriptomic data. For instance, RNA sequencing performed on cervical, thoracic and lumbar regions from post-mortem ALS patients, displayed a statistically significant down-regulation of lncRNAs in ALS patients, accounting for almost 55% of all the down-regulated genes and 15% of the up-regulated ones 36 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several tools for studying lncRNAs have been developed so far 33 , but a comprehensive understanding of their role and involvement in human diseases is still lacking. Despite a very few reports mentioned a role or a function directly attributed to lncRNAs in this disease 21,22,34,35 , some authors recently reported a differential expression of lncRNAs in ALS transcriptomic data. For instance, RNA sequencing performed on cervical, thoracic and lumbar regions from post-mortem ALS patients, displayed a statistically significant down-regulation of lncRNAs in ALS patients, accounting for almost 55% of all the down-regulated genes and 15% of the up-regulated ones 36 .…”
Section: Introductionmentioning
confidence: 99%
“…The involvement of RNA processing, metabolism and regulation in ALS pathogenesis has been described by numerous reports [14][15][16][17][18][19][20] , and the importance of ribostasis -the appropriate production and regulation of the cellular transcriptome -is further confirmed by the fact that many neuromuscular and neurodegenerative disorders are associated to alterations in protein folding, RNA regulation, RNA binding proteins, or RNP aggregates 17 . Such a scenario implies that distinct, yet uncovered, "molecular regulators" could be involved in ALS pathogenesis, including long non-coding RNAs (lncRNAs) 21,22 a novel class of transcripts whose main function relies on the regulation of biological functions related to cell differentiation and regeneration [23][24][25][26] . By definition, they are non-coding transcripts longer than 500 nucleotides, mostly generated by the RNA-Pol II 27 .…”
Section: Introductionmentioning
confidence: 99%